Women's ownership rights to landed property in Nigeria: key to economic empowerment. (4th September 2019) - Aluko, Yetunde Adebunmi
Using desk reviews and qualitative data collection methods, the paper critically examines the rights of women to own land in current Nigeria, with a specific look at the three major tribes, both under the Nigerian customary laws and statute; the problems faced by women in Nigeria as a result of lack of unhindered access to land in their fatherland; the effects of such denial on their level of economic empowerment; and its ripple effect on the crucial role of women to achieve sustainable development goals. The paper concludes by recommending an awakening of the consciousness of relevant stakeholders.